Adaptation of compact callus of pomelo (Citrus grandis) to liquid media as potential approach to increase growth - Zarina, Zakaria; Nor Alina, Nazri; Azlinda, Mohd Ali; Ku Syahidah, Ku Ismail; Mohd Azlan, Mohd Ishak (Sarawak Biodiversity Centre & Malaysian Biotechnology Corporation, 2010)
Biodiversity and Biotechnology Symposium 2008, 19th - 21st Nov 2008 organized by Sarawak Biodiversity Centre & Malaysian Biotechnology Corporation at Kuching, Sarawak, Malaysia.